2018
DOI: 10.1038/s41598-018-35548-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognosis of Coexisting Frailty and Cognitive Impairment in Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: The aim of this study was to investigate the prevalence of coexisting frailty and cognitive impairment and its association with clinical outcomes in patients on continuous ambulatory peritoneal dialysis (CAPD). Patients on CAPD started to enroll from 2014 to 2016 and ended follow-up by 2017. Frailty was assessed by clinical frailty scale (CFS), and cognitive function was assessed by Montreal Cognitive Assessment (MoCA). Totally 784 CAPD patients were recruited, with median duration of PD 30.7 (8.9~54.3) months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
2
8
0
3
Order By: Relevance
“…This phenomenon might be first explained by the underestimation of decline in cognitive function due to case bias from drop-outs (survivor bias). Other possible explanations for this phenomenon might be that participants included in this study had higher serum albumin levels (38.9 ± 3.2 g/l) as compared to those in previous studies [46]. Serum albumin level was an independently favorable factor to maintain the cognitive function as shown in our multicenter prospective cohort study [47].…”
Section: Discussionmentioning
confidence: 60%
“…This phenomenon might be first explained by the underestimation of decline in cognitive function due to case bias from drop-outs (survivor bias). Other possible explanations for this phenomenon might be that participants included in this study had higher serum albumin levels (38.9 ± 3.2 g/l) as compared to those in previous studies [46]. Serum albumin level was an independently favorable factor to maintain the cognitive function as shown in our multicenter prospective cohort study [47].…”
Section: Discussionmentioning
confidence: 60%
“…35,36 Our results are consistent with these prior findings and highlight the effect of TMAO on the overall condition of the older population by focusing on cognitive frailty because studies have shown that older adults with cognitive frailty have a worse prognosis than those with cognitive impairment only. 37 Currently, only long-term physical activity can reduce cognitive frailty, 38 and neither a biomarker nor a targeted intervention for cognitive frailty has been proposed. Therefore, considering TMAO as a predictor of cognitive frailty can provide a novel prospect for future research on improving cognitive frailty.…”
Section: Figurementioning
confidence: 99%
“…Prior studies have demonstrated that the presence of comorbid diseases and lower serum albumin levels are significant risk factors for mortality in elderly patients receiving PD [ 27 , 28 ]. Previously we reported that older age, diabetes, CVD and malnutrition are associated with both frailty and cognitive impairment among patients on continuous ambulatory PD and that the coexisting frailty and cognitive impairment is related to decreased patient survival rate [ 29 ]. In the present study, elderly patients in the early-start group had a higher proportion of diabetes and lower serum albumin compared with the late-start group, which may partly explain the increased mortality of elderly patients with early dialysis.…”
Section: Discussionmentioning
confidence: 99%